2016
DOI: 10.1016/j.chroma.2016.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of C1 and C4 oxidized oligosaccharides, the products of lytic polysaccharide monooxygenases acting on cellulose

Abstract: Lytic polysaccharide monooxygenases play a pivotal role in enzymatic deconstruction of plant cell wall material due to their ability to catalyze oxidative cleavage of glycosidic bonds. LPMOs may release different products, often in small amounts, with various oxidation patterns (C1 or C4) and with varying stabilities, making accurate analysis of product profiles a major challenge. So far, HPAEC has been the method of choice but it has limitations with respect to analysis of C4-oxidized products. Here, we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 30 publications
1
107
0
3
Order By: Relevance
“…5B. It is noteworthy that the native species observed with HPAEC may also originate from C-4-oxidized products, as it has recently been shown that C-4-oxidized products are unstable and tend to lose the oxidized monosugar under the chromatographic conditions used here (34). …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…5B. It is noteworthy that the native species observed with HPAEC may also originate from C-4-oxidized products, as it has recently been shown that C-4-oxidized products are unstable and tend to lose the oxidized monosugar under the chromatographic conditions used here (34). …”
Section: Resultsmentioning
confidence: 73%
“…Peaks were assigned based on previous assignments by Isaksen et al (50); native cello-oligosaccharides are labeled as Glc n , where n is the degree of polymerization (DP). Note that it has recently been shown that C-4-oxidized products are unstable under these chromatographic conditions and that the peaks labeled C-4 are, in fact, diagnostic degradation products (34). The fractions of native products are high because C-4-oxidized products tend to lose the oxidized monosugar under these chromatographic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher amounts of G2 were detected in the 1st h of the reaction, while after 24-h incubation, the main non-oxidized product was glucose. Regarding the release of oxidative products, peaks were assigned based on previous assignments [57, 58] and comparison with the activity patterns of Nc LPMO9C from Neurospora crassa [59] and Pc LPMO9D from Phanerochaete chrysosporium [60] (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…A more comprehensive discussion on PGC supports is available 30 , as is a more exhaustive discussion on comparisons between PGC supports versus reversed-phase and HILIC ones for glycan analysis 31 . Since PGC columns remain attractive for polar analytes, these packings have seen use in the separation of glycans isolated from mammalian sources 32,33 and have applications in the separation of other carbohydrates such as underivatized oligosaccharide anomers in vegetable matrices 34 , cello-oligosaccharides 35,36 and fructan mixtures 37 . While these PGC packings remain somewhat unexplored for carbohydrate purification, a few drawbacks associated with these supports have come to light, including the loss of retention/variability in retention times 31,38 and poor stability of the packing material under acidic mobile phase conditions 39 .…”
Section: Analytical Toolbox Of Chromatographic Modesmentioning
confidence: 99%